EXCISE TAX: PROBLEMS OF IMPROVEMENT - Shodiev Olimjon Abdurakhmаnovich (European Science Publishing, 2025)
The article examines the economic essence, features, fiscal significance and stages of reforming the excise tax, and also develops proposals for improving the administration of the excise tax.
Keywords: Tax system, taxes, taxation, excise tax, excisable goods, tax rate, excise stamp, state budget.